Analysis of technologies for repairing cracks in stone structures - MOLODID, Oleksandr; PLOKHUTA, Ruslana; MOLODID, Olena; BENDERSKYI, Sergiy (Ways to Improve Construction Efficiency, 2024)
In the process of technical inspections of buildings and structures, including those damaged as a result of military operations, it was found that the main damages of stone structures are cracks of different spatial position, width of opening, depth and length. Cracks can be caused by many different factors, such as subsidence of the base, for example, due to systematic wetting as a result of damage to the drainage system, mechanical stress, temperature, humidity and weathering, etc. In recent years, a significant number of buildings and structures in Ukraine have been subjected to off-design impacts, namely explosions. In this regard, as well as taking into account other factors, there is a need to find the optimal technology for repairing cracks in stone structures, which will not only fill the crack and restore the integrity of the structures, but also improve the performance of the restored structures, provide spatial stiffness if necessary, and at the same time be relatively simple to perform and have a relatively low cost of work. According to DSTU B B.3.1-2:2016, the main technologies for repairing structures with cracks include crack injection, introduction of reinforcement elements and full or partial replacement of masonry. The article discusses the most well-known repair technologies and outlines their advantages and disadvantages. The most commonly used technology is crack patching with repair mortars. However, this technology is effective only in the case of guaranteed stabilisation of crack formation. The classical technologies for repairing and strengthening structures include crack injection with repair solutions, the installation of cages (mortar, reinforced concrete, steel, combined) and ‘stitching’ cracks by installing steel elements (plates, rods, channels, etc.). A new direction in the reinforcement of structures is the ‘stitching’ of cracks with high-strength steel rods by inserting them into the body of structures using a ‘dry’ or ‘wet’ method and external reinforcement of structures with cracks using high-strength carbon reinforcement elements (fibres, fabrics, lamellas).